CRIMINAL PENALTY FOR EMPLOYEES WHO LEAVE COMPANY CONFIDENTIAL ACCORDING TO THE ELECTRONIC INFORMATION AND TRANSACTION LAW - Junaedi, Junaedi (International Journal of Social Science, 2022)
Company secrets are very essential; especially to prevent unfair business competition, from other business actors who own companies that produce similar goods or services, especially if it is related to the globalization of trade. So the legal protection of trade secrets will give birth to a form of honest business competition among business people and become a very valuable commodity because it has a high economic value; Employees who reveal or leak company secrets (Corporate Secrets which should be kept secret except for the interests of the state, either through print media (newspapers, magazines, bulletins), or online (TV, Instagram, YouTube, Snapchat (WhatsApp, SMS), Tik-Tok, Facebook and Twitter)) whose contents contain insults and/or defamation, shall be subject to criminal penalties based on Article 27 paragraph (3) in conjunction with Article 42 of Law No.19 of 2016 concerning Amendments to Law No.11 of 2008 concerning Information and Electronic Transactions are subject to a maximum imprisonment of 6 (six) years and/or a maximum fine of Rp. 1,000,000,000.00,- (one billion rupiah).